Q.1 Expand:

i) (2a+3b+4c)^2      

 = (4a^2  +9b^(2 )+16c^2) +2 (6ab+12bc+8ac)     

 = 4a^(2 )+9b^2+16c^2+12ab+24bc+16ac     

  \\     

 ii) (a+2b-5c)^2      

 = (a^2+4b^2+25c^2) +2 (2ab -10bc-5ac)      

 = a^2+4b^2+25c^2+4ab-20bc-10ac      

  \\     

iii)  (3x +2y-z)^2      

 = (9x^2+4y^2+z^2 )  +2 (6xy-2yz-6xz)      

 = 9x^2+4y^2+z^2+12xy-4yz-12xz      

  \\     

iv)  (3x-2y-1)^2     

 = (9x^2+4y^2+1)+ 2 (-6xy+2y-3x)      

 = 9x^2+4y^2+1-12xy+4y-6x      

  \\     

 v) (\frac{a}{2}-\frac{b}{3}+\frac{c}{4})^2     

 = (\frac{a^2}{4}+\frac{b^2}{9}+\frac{c^2}{16})+2(\frac{-ab}{6}-\frac{bc}{12}+\frac{ac}{8})     

 = (\frac{a^2}{4}+\frac{b^2}{9}+\frac{c^2}{16})-\frac{ab}{3}-\frac{bc}{6}+\frac{ac}{4}     

  \\     

 vi) (x-\frac{2}{x}+3)^2     

 = x^2 +\frac{4}{x^2} +9-2\times (-2-\frac{6}{x}+3x)     

 = x^2+\frac{4}{x^2} +9+4+\frac{12}{x}-6x     

 = x^2+\frac{4}{x^2} +\frac{12}{x}-6x+13     

  \\     

Q.2 If   (a+b+c)=10       and   ab+bc+ac = 31     Find   (a^2+b^2+c^2 )    

Answer:

  (a+b+c)^2=(a^2+b^2+c^2 )+2(ab+bc+ca)    

  (a^2+b^2+c^2 )=10^2-2\times 3=100-62=38    

  \\     

Q.3 If   ((a+b+c)=9     and   (a^2+b^2+c^2 )=29     find   (ab+bc+ac)    

Answer:

  (a+b+c)^2=(a^2+b^2+c^2 )+2(ab+bc+ac)    

  (ab+bc+ac)=\frac{1}{2} (9^2-29)=\frac{(81-29)}{2}=26    

  \\     

Q.4 If    (a^2+b^2+c^2 )=45     and    (ab+bc+ac)=38     find  (a+b+c)    

Answer:

  (a+b+c)^2=(a^2+b^2+c^2 )+2(ab+bc+ac)    

  (a+b+c)^2=45+2\times 38=121    

  (a+b+c)=11    

  \\     

Q.5 If   (a+b-c)= 11        and   (a^2+b^2+c^2 )=89        find   (ab-bc-ca)       

Answer:

  (a+b-c)^2=(a^2+b^2+c^2 )+2(ab-bc-ac)     

or   (ab-bc-ca)=\frac{1}{2} (81-11^2 )=-20     

  \\     

Q.6 Expanding using Formula       (a+b)^3=a^3+b^3+3ab(a+b)       

  i) (x+3)^3= x^3+27+9x(x+3)     

  = x^3+9x^2+27x+27     

  \\     

  ii) (4+a)^3=64+a^3+3\times4a (4+a)     

  = a^3+12a^2+12a+64     

  \\     

  iii) (6a+5b)^3= (6a)^3+(5b)^3+3(6a)(5b)(6a+5b)     

  =216a^3+125b^3+540a^2  b+450ab^2     

  \\     

Q.7 Expand Unity Formula   (a-b)^3=a^3-b^3-3ab(a-b)       

  (x-4)^3=x^3-64-12x(x-4)     

  = x^3-12x^2+48x-64     

  \\     

  (2-y)^3=8-y^3-4y(2-y)     

  = -y^3+4y-8y+8     

  \\     

  (4x-5y)^3=64 x^3-125y^3-60xy(4x-5y)     

  =64x^3-125y^3-240x^2 y+300 xy^2     

  \\     

Q.8 Evaluate the following:-

a)  \ \ 103^3=(100+3)^3=1000000+27+900(100+3)     

  = 1000000+27+92700     

  = 109272.7     

  \\     

 b) \ \  98^3=(100-2)^3=1000000-8-600(100-2)     

  = 1000000-8-58800     

  =941192     

  \\     

c)  \ \  402^3=(400+2)^3=64000000+8+2400(400+2)     

  = 64964808     

  \\     

d) \ \  598^3=(600-2)^(3 )=216000000-8-3600(600-2)     

  = 216000000-8-2152800     

  = 213847192     

  \\     

Q.9 If (a+\frac{1}{a})=6,       find  the value of  (a^3+\frac{1}{a^3})      

Answer:

  (a+\frac{1}{a})^3= a^3+ \frac{1}{a^3} +3 (a+\frac{1}{a})    

  or\ \  a^3+\frac{1}{a^3} =6^3-36=198    

  \\     

Q.10 If   (2a +\frac{1}{2a})=4      Find the value of    (8a^3+ \frac{1}{8a^3} )      

Answer:

  (2a +\frac{1}{2a})^3=8a^3+ \frac{1}{8a^3}+3(2a +\frac{1}{2a})    

  or \ \ 8a^3+ \frac{1}{8a^3}=4^3-3\times 4=64-12=52    

  \\     

Q.11 If   (x- \frac{1}{x})=7        Find the value of   (x^3- \frac{1}{x^3} )       

Answer:

   (x- \frac{1}{x})^3=x^3- \frac{1}{x^3}   -3(x- \frac{1}{x})    

  \ \ or x^3- \frac{1}{x^3} =7^3+3\times 7=343 +21=364    

  \\     

12 If   (3p- \frac{1}{3p})=5,        Find the value of  (27p^3- \frac{1}{27 p^3})       

Answer:

  (3p- \frac{1}{3p})^3= (27 p^3-\frac{1}{27 p^3} )-3 (3p- \frac{1}{3p})    

  or \ \  (27p^3-\frac{1}{27 p^3})=5^3+3\times 5=125 + 15 =140    

  \\     

Q.13 If   a + b = 9       and   ab=20       find the value of   a^3+b^3       

Answer:

(a+b)^3 = a^3+b^3+3ab(a+b)

  or \ \  a^3+ b^3= 9^3-3\times 20\times 9=189    

  \\     

Q.14 If  (2x + 3y) = 7       and   xy=2       find the value of   (8x^3+27y^3 )       

Answer:

  (2x+3y)^3= 8x^3+27y^3+18 xy (2x+3y)    

  8x^3+27y^3=7^3-18\times 2\times 7=91    

  \\     

Q.15 If   (a-b)=5       and   ab=14       Find the value of   (a^3-b^3)       

Answer:

   (a-b)^3  = (a^3-b^3 )-3ab(a-b)    

  a^3-b^3=5^3-3\times 5\times 14=-85    

  \\     

Q.16 If   (4x-5z)=2       and   xz=6       find the value of   (64x^3  -125z^3)       

Answer:

   (4x-5z)^3=64x^3  -125x^3  -60xz (4x-5z)    

64^3-125^3=23+60 \times 6 \times 2 = 728

  \\     

Advertisements